The Alternative Imaging Modalities in Ischemic Heart Failure (AIMI-HF) Trial—IMAGE HF Project 1A - Mielniczuk, Lisa M.; O’Meara, Eileen; Wiefels, Christiane; Chen, Li; Garrard, Linda; White, James; deKemp, Robert A.; Di Carli, Marcelo F.; Larose, Eric; Paterson, David I.; Ezekowitz, Justin; Kandolin, Riina M.; et al. (Elsevier BV, 2026)
Background: The role of advanced (cardiac magnetic resonance [CMR] or positron emission tomography [PET]) vs single-photon emission computerized tomography (SPECT) ischemia imaging to guide management remains unclear in patients with ischemic heart failure (IHF). The primary aim was to determine the effect of imaging modality on a composite cardiovascular endpoint and cardiac death in patients with IHF who require ischemia assessment.
Methods: Patients with IHF were randomized to advanced or SPECT imaging. A parallel registry also was performed. The primary endpoint was the composite of cardiac death, infarction, arrest, and cardiac rehospitalization. The key secondary endpoint was cardiac death.
Results: Patients in the randomized population (advanced imaging [PET or CMR; n = 64] or SPECT [n = 56]) had a cumulative incidence rate (CIR) for the primary endpoint of 33.1% and 33.0%, respectively (hazard ratio [HR] 0.94, 95% confidence interval [CI] 0.49, 1.80, P = 0.853). CIRs for cardiac death were 13.8% and 25.1%, respectively (HR 0.62, 95% CI 0.25, 1.80, P = 0.296). In the parallel registry (n = 336 advanced; n = 216 SPECT), the primary endpoint CIRs were 31.2% and 35.3%, respectively (HR 0.81, 95% CI 0.56, 1.19, P = 0.284). CIRs for cardiac death were 11.0% and 16.6%, respectively (HR 0.53, 95% CI 0.27, 1.04, P = 0.066). Patients were followed for a median (interquartile range) of 24.1 (11.6, 27.5) months. Pooled analysis from the randomized and registry populations revealed a significant benefit of advanced imaging for reduction of cardiac death (HR 0.56, 95% CI 0.33, 0.96, P = 0.04) with minimal heterogeneity (I2 = 0%).
Conclusion: Among IHF patients assessed for ischemia, advanced imaging (PET or CMR) was not associated with reduced composite cardiac events, compared to SPECT.
Clinical Trial Registration: NCT01288560.